2009
DOI: 10.1002/jcu.20609
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured intramuscular ganglion cyst in the gastrocnemius medialis muscle: Sonographic appearance

Abstract: We report the case of a 55-year-old woman who presented with a severe pain and a mass in the proximal portion of the medial calf. On sonography, the lesion appeared as a poorly defined hypoechoic lesion with interspersed muscle bundles. A total excision of the lesion was performed. On microscopic examination, the specimen demonstrated cystic lesions surrounded by fibrous walls within the muscle bundles. A ruptured intramuscular ganglion cyst diagnosis was made based on the histopathologic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Ganglions cysts arise from joints in most cases and rarely from the tendon sheath, cartilage, cruciate ligaments, nerves, and muscles5-7). They have no communication with adjacent joint capsules in 30% of the cases5,7,8).…”
Section: Discussionmentioning
confidence: 97%
“…Ganglions cysts arise from joints in most cases and rarely from the tendon sheath, cartilage, cruciate ligaments, nerves, and muscles5-7). They have no communication with adjacent joint capsules in 30% of the cases5,7,8).…”
Section: Discussionmentioning
confidence: 97%
“…Various theories have been put forward to explain the occurrence of rare Intramuscular ganglion cysts. [4][5][6] Some opinion that these are sequestration cysts formed by the seepage of joint fluid from a defect on the surface of a tendon and leading to pooling up within the intramuscular plane forming a fluid like collection or pseudocyst. These kinds of cysts have been termed intramuscular dissecting ganglion cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [25] reported a case of ruptured intramuscular ganglion cyst in the gastrocnemius medialis muscle. Nicholson et al [24] also described a case of intramuscular ganglion cyst in the medial gastrocnemius muscle.…”
Section: Intramuscular Cysts Arising From the Muscular Tissuementioning
confidence: 99%
“…Based on previous case reports, we deduced that these intramuscular ganglion cysts arise from the muscular tissue. For this type of cysts, satisfactory clinical results can be achieved by direct open excision [19,24,25].…”
Section: Intramuscular Cysts Arising From the Muscular Tissuementioning
confidence: 99%